2015
DOI: 10.1016/j.ahj.2014.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Association between anger and mental stress–induced myocardial ischemia

Abstract: Background Mental stress-induced myocardial ischemia is associated with adverse prognosis in coronary artery disease patients. Anger is thought to be a trigger of acute coronary syndromes and is associated with increased cardiovascular risk; however, little direct evidence exists for a link between anger and myocardial ischemia. Methods [99mTc]sestamibi single-photon emission tomography was performed at rest, after mental stress (a social stressor with a speech task), and after exercise/pharmacological stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 29 publications
(32 reference statements)
1
33
1
1
Order By: Relevance
“…The first hypothesis regarding aggression and their associations with women's mental health was supported that aggression was related to low level of mental health. This is consistent with the findings of previous researches [28] [29] which have shown that aggression is associated with mental illness. The second hypothesis regarding the moderating effect of occupation on the relationship between aggression and mental health was not supported.…”
Section: Resultssupporting
confidence: 93%
“…The first hypothesis regarding aggression and their associations with women's mental health was supported that aggression was related to low level of mental health. This is consistent with the findings of previous researches [28] [29] which have shown that aggression is associated with mental illness. The second hypothesis regarding the moderating effect of occupation on the relationship between aggression and mental health was not supported.…”
Section: Resultssupporting
confidence: 93%
“…Emotional reactivity in everyday life, as well as anxiety and depression, have been associated with myocardial ischemia during mental stress but, in general, not with exercise-induced ischemia (Boyle et al, 2013; Burg et al, 2014; Carels et al, 1999; Wei et al, 2014a). Aggressive responding, hostile affect, and trait and state anger also have been associated with MSIMI (Burg et al, 1993; Pimple et al, 2015). …”
Section: Potential Mechanismsmentioning
confidence: 99%
“…It has been reported that anger, both as an emotional state and as a personality trait, is significantly associated with the propensity to develop myocardial ischemia. [ 7 ] It has been shown that chest pain is more frequent in patients with Type D personality. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%